Knowledge That Shapes Migratory Trajectories: Narratives of Colombian Migrant Women in Chile [Saberes Que Configuran Trayectorias Migratorias: Narraciones de Mujeres Colombianas Migrantes en Chile] - Contreras-Salinas, S (Universidad Autonoma del Estado de Mexico, 2019)
The objective of this research is to disclose the knowledge that six Colombian professional women display in their migratory trajectories in Chile, particularly in upbringing process. From the narrative approach, a case study method was resorted to through interviews. Among the results obtained, it is revealed that the legitimacy of migrant women is conditional on fulfilling their role as workers, with merit and effort gaining strength. Likewise, knowledge that resists the colonial matrix is recognized, displaying diverse strategies recreated in the processes of upbringing, considering them necessary for the welfare of the children. It is concluded that the discovery of knowledge triggers a multiplicity of experiences that put tension in the prevailing forms of neo-capitalism, warn about the subtle disciplinary practices and reveal resistance practices, contributing to scientific thinking with the possibility of distancing oneself from a binary and hierarchical ideology regarding the local and universal. © 2019 Universidad Autonoma del Estado de Mexico. All rights reserved.